Photodegradation of synthetic organic dyes in water using tungsten disulfide and bismuth-based metal halide perovskite composite materials - Mabilane, Tshegofatso (University of the Witwatersrand, Johannesburg, 2024)
Synthetic organic dyes (SODs) are extensively used in the textile, paint, and printing industries. However, these dyes pose significant threats to the ecosystem. The degradation of SODs through photocatalysis has garnered considerable attention from researchers as a promising approach for wastewater treatment and environmental remediation. This research project aims to investigate the photodegradation of methyl red and rhodamine B as anionic and cationic types of SODs respectively, using a metal halide perovskite (MHP), Cs3Bi2Br9. Then, the photodegradation efficacy of Cs3Bi2Br9 was compared to that of a heterostructure, composed of Cs3Bi2Br9 and a transition metal dichalcogenide (TMDC), WS2. Cs3Bi2Br9 and WS2 were synthesized using hotinjection, and colloidal synthesis methods, respectively. The synthesized materials were characterized using transmission electron microscopy (TEM), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), elemental mapping, ultraviolet-visible (UV-Vis) spectroscopy, Brunauer-Emmett-Teller (BET) analysis, zeta potential, powder X-ray diffraction (PXRD), and thermogravimetric analysis (TGA). Degradation experiments were conducted under controlled conditions, including varying catalyst loading (0.8 mg/mL, 1.6 mg/mL, and 2.4 mg/mL), initial dye concentrations (20, 40, and 60 ppm), and pH levels (pH 2, 7, and 12) to find the optimum dye photodegradation conditions. Photolysis studies were also carried out to assess the photolytic stability of the dyes. The oxidizing effect of adding 0.3519 M hydrogen peroxide to the photolysis and heterogeneous photocatalytic reactions was also investigated. When compared to Cs3Bi2Br9, the heterostructure, Cs3Bi2Br9/WS2, offered the advantages of improved dye degradation efficiency and stability due to enhanced charge separation. This is because WS2 is a layered material that has pockets that increase catalytic active sites thus making it a good co-catalyst. This project's findings shed light on the photocatalytic degradation of anionic and cationic dyes using a MHP and a heterostructure comprised of a MHP and TMDC. These findings contribute to the development of efficient and environmentally friendly approaches for SOD removal in wastewater.
A dissertation submitted in partial fulfilment of the requirements for the degree of Master of Science in Chemistry, to the Faculty of Science, School of Chemistry, University of the Witwatersrand, Johannesburg, 2024
Keywords: Metal halide perovskite; Transition metal dichalcogenide; Photocatalysis; Photodegradation; Synthetic organic dyes; Heterostructure; UCTD; SDG-6: Clean water and sanitation; SDG-13: Climate action